Chinese Concept of” Qi” and Military Wisdom - Tso, Hei Sing (PT. Civil Military Center, 2025)
Many people know about Sun Tsz’s “Art of War”. Sun Tsz is only one member of the Military School in Ancient Chinese thought. The concept of “Qi” or “Vital energy” or “Life force” is one of the core ideas in works of many members of the Military School throughout Chinese History. In this article, the concept of “Qi” is introduced in the military context, with reference to army governance and military tactics. We should appreciate the relevance of “Qi” in contemporary setting of warfare, security and geopolitics. Ancient wisdom is still valuable beyond the 21st century.